Avaliação da inclinação do incisivo inferior através da tomografia computadorizada - Filho, Leopoldino Capelozza [UNESP] (2008)
Introduction: Orthodontics has always used lateral cephalometric radiographs (LC) as the main examination in the orthodontic diagnosis and treatment plan. The determination of incisor position is part of most cephalometric analysis, including Tweed analysis. However, all radiographic images have limitations, since it is a bidimensional image of a tridimensional structure and overlapping of bone and dental structures often occurs. Computed tomography (CT) allows a trustworthy diagnostic, mainly for its tridimensional images possibility. In this situation it seems reasonable to question the classic cephalometric analysis, creating factors of comparison with computed tomography data. Aim: For this, it was considered the evaluation of the angle between the long axis of the inferior incisor and the mandibular plane (IMPA) in the lateral cephalograph and in the computed tomography. Methods: Nineteen patients, selected for orthodontic treatment, had constituted the sample of this study, 12 female and 7 male, with ages between 16 years and 4 months and 28 years and 2 months. After the collection of data made by two examiners, statistical analyses for the attainment of the errors intra and inter-examiners had been made, using level of significance of 5%. Results and Conclusion: It was concluded that IMPA can be measured in the lateral cephalometric radiographs with trustworthiness, even that its values were smaller when compared with the computed tomography.